Biosensors for Food Toxin Detection: Carbon Nanotubes and Graphene. Issue 1725 (27th February 2015) - Malhotra, Bansi D.; Srivastava, Saurabh; Augustine, Shine
ABSTRACT: There is increased interest towards the application of carbon based nanomaterials to biosensors since these can be used to quickly detect presence of the toxins in food, agricultural and environmental systems. The accurate, faster and early detection of food toxins is presently very important for ensuring safety and shelf life of agricultural commodities resulting from food contamination. The carbon materials (CNTs) and recently discovered graphene have been predicted to be promising candidates in the development of electrochemical biosensor owing to their exceptionally large surface area and interesting electrochemical properties. We focus on some of the recent results obtained in our laboratories pertaining to the development of biosensors based on multi-walled carbon nanotubes and graphene for mycotoxin(aflatoxin ) detection.